Human adeno-associated virus type 5 is only distantly related to other known primate helper-dependent parvoviruses - Bantel-Schaal, Ursula; Delius, Hajo; Zur Hausen, Harald (Journal of virology, 1999)
We have characterized 95% (4,404 nucleotides) of the genome of adeno-associated virus type 5 (AAV5), including part of the terminal repeats and the terminal resolution site. Our results show that AAV5 is different from all other described AAV serotypes at the nucleotide level and at the amino acid level. The sequence homology to AAV2, AAV3B, AAV4, and AAV6 at the nucleotide level is only between 54 and 56%. The positive strand contains two large open reading frames (ORFs). The left ORF encodes the nonstructural (Rep) proteins, and the right ORF encodes the structural (Cap) proteins. At the amino acid level the identities with the capsid proteins of other AAVs range between 51 and 59%, with a high degree of heterogeneity in regions which are considered to be on the exterior surface of the viral capsid. The overall identity for the nonstructural Rep proteins at the amino acid level is 54.4%. It is lowest at the C-terminal 128 amino acids (10%). There are only two instead of the common three putative Zn fingers in the Rep proteins. The Cap protein data suggest differences in capsid surfaces and raise the possibility of a host range distinct from those of other parvoviruses. This may have important implications for AAV vectors used in gene therapy.